Context-Dependent Effects of a Single Administration of Mirtazapine on the Expression of Methamphetamine-Induced Conditioned Place Preference - Voigt, Robin; Napier, T. Celeste (Frontiers in Behavioral Neuroscience, 2012)
Re-exposure to cues repeatedly associated with methamphetamine (Meth) can trigger Meth-seeking and relapse in the abstinent abuser. Weakening the conditioned Meth-associated memory during cue re-exposure may provide a means for relapse-reduction pharmacotherapy. Accordingly, we sought to determine if the atypical antidepressant mirtazapine disrupted the long-term maintenance of Meth-induced conditioned place preference (CPP) when administered in conjunction with re-exposure to contextual conditioning cues, and if this effect was altered by Meth being present during cue re-exposure. First, we evaluated the effect of mirtazapine on the maintenance of Meth-induced CPP during re-exposure to either the saline- or Meth-paired chamber 12 days after conditioning. Meth conditioned rats subsequently administered mirtazapine expressed CPP independent of re-exposure to the saline- or Meth-paired chamber; but the magnitude of CPP was significantly less for mirtazapine-treated rats re-exposed to the Meth-paired chamber. Next, we evaluated the effect of mirtazapine on a ‘reinforced re-exposure’ to the Meth-paired context. Administration of mirtazapine vehicle and Meth, prior to re-exposure to the Meth-paired chamber did not disrupt the ability of rats to demonstrate CPP on day 20; however, rats administered mirtazapine and Meth prior to re-exposure to the Meth-paired chamber did not demonstrate CPP. These results indicate a context-dependent effect of mirtazapine, and that the ability of mirtazapine to disrupt the long-term maintenance of CPP is greatest when the atypical antidepressant is tested with a combination of Meth injection and contextual cues.